2010
DOI: 10.1128/mbio.00061-10
|View full text |Cite
|
Sign up to set email alerts
|

Global Warming Will Bring New Fungal Diseases for Mammals

Abstract: Fungi are major pathogens of plants, other fungi, rotifers, insects, and amphibians, but relatively few cause disease in mammals. Fungi became important human pathogens only in the late 20th century, primarily in hosts with impaired immunity as a consequence of medical interventions or HIV infection. The relatively high resistance of mammals has been attributed to a combination of a complex immune system and endothermy. Mammals maintain high body temperatures relative to environmental temperatures, creating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
209
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(219 citation statements)
references
References 38 publications
2
209
0
8
Order By: Relevance
“…To our knowledge, this is the first demonstration of the growth of any microbe during extreme freeze-thaw cycles, although activity of microbes during such cycles has long been known (reviewed in Schmidt et al 2009a). The ability to survive and thrive within a very broad temperature range may be a characteristic widespread within the Tremellomycetes; even pathogenic Cryptococcus gatti and C. neoformans exhibit broad tolerance to a range of temperatures (Nichols et al 2007, Garcia-Solache and Casadevall 2010), but have not been shown to be able to grow at subfreezing or fluctuating temperatures like members of the genus Naganishia .…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 99%
“…To our knowledge, this is the first demonstration of the growth of any microbe during extreme freeze-thaw cycles, although activity of microbes during such cycles has long been known (reviewed in Schmidt et al 2009a). The ability to survive and thrive within a very broad temperature range may be a characteristic widespread within the Tremellomycetes; even pathogenic Cryptococcus gatti and C. neoformans exhibit broad tolerance to a range of temperatures (Nichols et al 2007, Garcia-Solache and Casadevall 2010), but have not been shown to be able to grow at subfreezing or fluctuating temperatures like members of the genus Naganishia .…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 99%
“…Additional evidence for this concept comes from studies of insect fungal pathogens, which suggest that the capacity for insect pathogenicity may follow preadaptation from interactions with amoebae in the environment (4). Understanding the mechanisms by which virulence emerges in environmental microbes is important considering that global warming has been hypothesized to bring about new fungal diseases in the coming century (13).…”
mentioning
confidence: 99%
“…However, infections of otherwise healthy people are on the rise. Global warming is inducing rapid poleward movement of crop fungal pathogens, and may also increase the prevalence of fungal disease in humans as fungi adapt to survival in warmer temperatures 4 . In this scenario, increasing resistance to the limited arsenal of antifungal drugs is a serious concern 5 , especially for Candida and Aspergillus infections, for which the therapeutic options have become limited.…”
mentioning
confidence: 99%